Addressing Identity Tensions Through Paradoxical Thinking: Lessons from Artistic Interventions in Organizations - Berthoin Antal, Ariane; Debucquet, Gervaise; Fremeaux, Sandrine (Management international / International Management / Gestiòn Internacional, 2016)
In organizational contexts characterized by multiple logics spanning from conformity to innovation, many employees experience tensions between a business-like identity and an artistic identity. The contribution uses data generated from Web-based surveys of employees, managers, and artists in 86 Spanish companies to explore how identity tensions can be addressed with paradoxical thinking. It shows that engaging in artistic interventions can help people accept and deal with identity tensions between self-and-other and between conformity-creativity in the workplace, enabling the removal of real or subjective barriers to generating new ways of collaborating, new ideas and new ways of doing things.